1983
DOI: 10.1002/ajmg.1320140210
|View full text |Cite
|
Sign up to set email alerts
|

Search for a red cell enzyme or serum protein marker in amyotrophic lateral sclerosis and parkinsonism‐dementia of guam

Abstract: Frequency distributions were determined for 24 red cell enzyme and four serum protein systems, in an attempt to identify a genetic marker associated with either amyotrophic lateral sclerosis (ALS) or parkinsonism-dementia (PD), two progressive and fatal neurological disorders of unknown cause found with unusually high incidence among the Chamorros of Guam and the Northern Mariana Islands. No striking associations were identified between either disorder and any of the gene markers tested. Thus, no genetic cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The Al/DNA-P ratio of whole, normal, human neuron cell nuclei (not only the heterochromatin) was, according to the quoted investigation, 700 ,ug/g DNA-equivalent to an Al/DNA-P molar ratio of 0.008 (106). A simple calculation shows that this must be a high ratio.…”
Section: Lymphocytesmentioning
confidence: 92%
“…The Al/DNA-P ratio of whole, normal, human neuron cell nuclei (not only the heterochromatin) was, according to the quoted investigation, 700 ,ug/g DNA-equivalent to an Al/DNA-P molar ratio of 0.008 (106). A simple calculation shows that this must be a high ratio.…”
Section: Lymphocytesmentioning
confidence: 92%
“…Originally, it was believed that this disease is an autosomal dominant disorder with complete penetrance in males and ~50% penetrance in females [65]. However, as no marker system associated with this disorder was found, it has been concluded that "local environmental factors are most likely involved in pathogenesis" [68,69]. This hypothesis was supported by the fact that the high incidence of ALS/PD in Guam disappeared when isolation was disrupted and travel and economic changes brought food and water sources from the outside.…”
Section: -Synuclein In Dlb and Other Lewy Body Disordersmentioning
confidence: 98%
“…Epidemiological studies mostly support an environmental factor, connected to the traditional life pattern, as a probable cause of the disease. A higher incidence was observed on Guam than on the other nearby islands and it was greatest in some ofthe most southern villages, reported to be least westernized (682,699,700).…”
Section: Diseases With Proposed Al3" Connectionmentioning
confidence: 84%